Selling the Empire?: Marketing and the Demise of the British World, c.1920–1960. Issue 4 (3rd July 2020) - Thackeray, David
ABSTRACT: This article uses a study of the politics of marketing and advertising to consider the role that British World collaboration played in consumer politics in the UK and the Dominions between the 1920s and 1950s. We will assess how politicians and businesspeople in the Dominions responded to the Empire Marketing Board's efforts to encourage the habit of 'Buying British' in the inter-war years, as well as exploring the activities of the leading American marketing agency, J. Walter Thompson. The article concludes with a discussion of how the politics of patriotic trade was recast in the 1950s. While this was a cause which had taken on different forms in Australia, Canada and South Africa during the 1930s, in each country its advocates shared a wider concern with imperial development. And yet, changes in the advertising and marketing industries, and the growth of market research, cut across efforts to promote the consumer habit of buying imperially. By the early 1960s patriotic trade campaigns in the 'old' Dominions were nationally focused and shorn of their earlier 'Britannic' identity.